Study of ECG changes and left ventricular diastolic dysfunction as hemodynamic markers of myocardial stress in chronic smokers - Sandhya, Metta; Satyanarayana, Uppala; Joyarani, Deverashetty (International Journal of Research in Medical Sciences, 2017)
Background: Nicotine being the chief component of cigarette smoke, is a potent inhibitor of the cardiac A type potassium channels, which contributes to the changes in the electrophysiology of heart and affects the cardiac diastolic functions. The present study was undertaken to evaluate the ECG changes, left ventricular diastolic functions and dyslipidemia in chronic smokers. Methods: 127 healthy male volunteers without any systemic illnesses, drug or alcohol intake, in the age group of 20-60 years, who attended the outpatients department of a tertiary care government hospital were recruited for the study. They were subsequently divided into smoker group consisting of 64 subjects with ≥20 pack years of smoking duration and the non-smoker group consisting of 63 subjects, who were never smokers. All the subjects were evaluated for lipid profile and 2D echocardiography was done to assess the Left Ventricular Ejection Fraction (LVEF). The ECG was recorded for all the subjects and parameters such as the heart rate, the PR interval and the QRS complex and ST interval were assessed in seconds. The QTc (corrected QT interval) was calculated by using Bazet’s formula. Results: The lipid profile of smokers indicated significantly high Total Cholesterol, LDL, VLDL, TG and significantly low levels of HDL in comparison to non-smokers. (p<0.001) The ECG and echocardiography analysis showed significant increase in the heart rate and shortening of QRS complex and ST interval along with significant reduction in LVEF (P <0.001) in the smokers. Conclusion: Along with conventional markers of dyslipidemia, shortening of QRS complex, ST segment and reduced LVEF should be considered as markers of myocardial stress in chronic smokers while screening them for risk of coronary artery disease.